Initial Experience With Transoral Endoscopic Thyroidectomy via the Submental and Vestibular Approach for the Treatment of Thyroid Cancer: A Retrospective Cohort Study - Wang, Yuanyuan; Fu, Yilong; Wu, Guoyang; Luo, Yezhe; Yan, Chaolong; Fu, Jinbo; Lin, Suqiong (Frontiers in Surgery, 2022)
Background: Transoral endoscopic thyroidectomy vestibular approach is feasible and safe but has some unavoidable limitations, such as sensory changes in the center of the chin region. We aim to report our initial experience in performing transoral endoscopic thyroidectomy via the submental and vestibular approach for the treatment of thyroid cancer. Patients and methods: This retrospective cohort study included patients with thyroid cancer confirmed by fine-needle aspiration who underwent endoscopic thyroidectomy and central lymph node dissection via the submental and vestibular approaches between November 2019 and January 2020. Patients’ clinicopathological characteristics, operation details, and postoperative complications were analyzed. Results: Fifteen surgeries were performed successfully. The mean ± standard deviation age of the patients was 37 ± 10.8 years, the average duration of surgery was 146.5 ± 34.6 min, and the median intraoperative blood loss was 11.1 ± 6.3 ml. None of the surgeries were converted to open thyroidectomy. According to postoperative pathology, all cases involved papillary thyroid carcinoma or papillary thyroid microcarcinoma. One patient developed transient recurrent laryngeal nerve paralysis. No patient developed skin numbness at the center of the chin region. Conclusions: Transoral endoscopic thyroidectomy via the submental and vestibular approach is effective and safe in patients with thyroid cancer and does not lead to skin numbness at the center of the chin region. This technique is beneficial for surgeons less experienced in performing transoral thyroid surgery as it involves using a short and direct route to the thyroid gland, which can reduce the difficulty in establishing the first operative space to some extent.